Differences in Cancer Death Risk Long After ACS Among Selected Urban and Rural Areas in North Italy: The ABC-7a† Study on Heart Disease - Mahmoud, Heba T.; Berton, Giuseppe; Cordiano, Rocco; Palmieri, Rosa; Nardi, Tobia; Abdel-Wahab, Mohammad AK; Cavuto, Fiorella (Frontiers in Oncology, 2021)
Background An increased risk of cancer death has been demonstrated for patients diagnosed with acute coronary syndrome (ACS). We are investigating possible geographic risk disparities. Methods This prospective study included 541 ACS patients who were admitted to hospitals and discharged alive in three provinces of Italy’s Veneto region. The patients were classified as residing in urban or rural areas in each province. Results With 3 exceptions, all patients completed the 22-year follow-up or were followed until death. Urban (46%) and rural (54%) residents shared most of their baseline demographic and clinical characteristics. Pre-existing malignancy was noted in 15 patients, whereas 106 patients developed cancer during the follow-up period, which represented 6232 person-years. No difference in the cancer death risk was found between the urban and rural areas or between southern and northern provinces (hazard ratio [HR] 1.1; 95% confidence interval [CI] 0.7–1.7; p = 0.59 and HR 1.1; 95% CI 0.9–1.4; p = 0.29, respectively) according to the unadjusted Cox regression analysis. Geographic areas, however, showed a strong positive interaction, with risk increasing from the urban to rural areas from southern to northern provinces (HR 1.9; 95% CI 1.1–3.0; p = 0.01). The fully adjusted Cox regression and Fine-Gray competing risk regression models provided similar results. Interestingly, these results persisted, and even strengthened, after the exclusion of the 22 patients who developed malignancy and survived to the end of follow-up. We did not observe an urban/rural difference in non-neoplastic death risk or a significant interaction between the geographic areas. Conclusion Our analysis reveals that the cancer death risk among unselected ACS patients in Italy’s Veneto region significantly differs by geography. The northern rural area has the highest risk. These results highlight the importance of implementing a preventive policy based on area-specific knowledge.